The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0363546515597668
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Glenoid Defects and Hill-Sachs Lesions in Shoulders With Traumatic Anterior Instability

Abstract: The prevalence of bipolar lesions was approximately 60%. As glenoid defects became larger, Hill-Sachs lesions also enlarged, but there was no strong correlation. Bipolar lesions were frequent in patients with recurrent instability, patients with repetitive dislocation/subluxation, and those playing collision/contact sports. Instability showed a high recurrence rate in shoulders with bipolar lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 28 publications
3
59
0
Order By: Relevance
“…16,40,49 More complex osseous lesions must be critically evaluated to ensure comprehensive management. While the glenoid has traditionally been the area of focus, characteristics of the Hill-Sachs lesion have recently received increased attention.…”
Section: Managementmentioning
confidence: 99%
“…16,40,49 More complex osseous lesions must be critically evaluated to ensure comprehensive management. While the glenoid has traditionally been the area of focus, characteristics of the Hill-Sachs lesion have recently received increased attention.…”
Section: Managementmentioning
confidence: 99%
“…Evidence has emerged that this is in actual fact a bipolar phenomenon that affects up to 56% of cases. 46 The epileptic population is prone to such defects because of multiple, vigorous seizures resulting in dislocations or subluxations that occur with considerable force. 10,67 Understanding of this relatively new concept is essential in deciding on the precise operative strategy to employ because such lesions further potentiate instability owing to their combined effect on glenohumeral translation.…”
Section: Bipolar (Glenoid and Humeral) Bone Lossmentioning
confidence: 99%
“…In a retrospective radiographic analysis of 153 shoulders before Bankart repair, Nakagawa et al 46 found bipolar bone loss in 56% of the cohort. As the glenoid defect became larger, the Hill-Sachs lesion also increased in size, although there was little correlation between the two.…”
Section: Bipolar (Glenoid and Humeral) Bone Lossmentioning
confidence: 99%
“…Although postoperative instability recurrence was noted as 0% in patients with no bony lesion, a 29.4% recurrent rate was seen in patients with bipolar lesions. 3 Furthermore, in 33 patients with primary instability and 111 patients with recurrent instability, a significant difference was shown in the prevalence of Hill-Sachs lesions and inverted pearshaped glenoid lesions. 4 This reaffirms the findings of Arciero et al 5 showing an additive and negative effect on glenohumeral stability as a result of combined glenoid and humeral head defects.…”
mentioning
confidence: 97%
“…In 103 shoulders, Nakagawa et al 3 showed an incidence rate of bipolar lesions (bony lesion at both the glenoid and humeral head) in 33.3% of all shoulders with primary instability and 61.8% of all shoulders with recurrent instability. Although postoperative instability recurrence was noted as 0% in patients with no bony lesion, a 29.4% recurrent rate was seen in patients with bipolar lesions.…”
mentioning
confidence: 99%